ETHNICITY, POLICY CHOICE AND IMPLEMENTATION IN NIGERIA: A DISCOURSE ON RANCH GRAZING - UGBUDU, Martin Iorgbir (Socialscientia: Journal of Social Sciences and Humanities, 2018)
Violent clashes between Fulani herdsmen and rural farmers have become a recurring decimal in Nigeria since the return to civil rule in 1999. These have left death tolls, rendered thousands homeless and aggravated communal conflicts and insecurity in the country. Amongst a plethora of options, the establishment of ranches has been mooted as a solution to the problem. This paper is a prognosis on the proposed ‘Ranch Grazing’ policy. The central thesis of the paper is that, inter-ethnic rivalry over political dominance to determine who gets what and how has permeated and corrupted the policy-making arena to the extent that what becomes the prime determinant in the choice of policy and its implementation is the perceived sectional rather than national gain from such a policy. Against this policy milieu, the paper seeks to address the import of the ranch-grazing policy; the group contestations over the establishment of ranches as well as predict the outcome of the policy. Addressing these issues will bring to fore the core issues of misunderstanding that arise between various ethnic groups in the country in the quest of forging a modern state that conduces to the realization of the yearnings and aspirations of the citizens. The study which is analytical relies on secondary data sources and is anchored on the Group Theory. It recommends among other things that policy makers should be guided by national interest and the quest for development in the choice of policy rather than sectional/ethnic interest.